Learning Impacts of Pretraining Video-Assisted Debriefing With Simulated Errors or Trainees' Errors in Medical Students in Basic Life Support Training: A Randomized Controlled Trial. Issue 6 (December 2019) - Li, Qi; Lin, Jing; Fang, Li-Qun; Ma, Er-Li; Liang, Peng; Shi, Ting-Wei; Xiao, Hong; Liu, Jin
Abstract : Background: Previous studies demonstrated that pretraining video-assisted debriefing (VAD) with trainees' errors (TE) videotaped in a skills pretest improved skill learning of basic life support (BLS). However, conducting a pretest and preparing TE video examples is resource intensive. Exposing individual trainee's errors to peers might be a threat to learners' psychological safety. We hypothesized pretraining VAD with simulated errors (SE, performed by actors) might have the same beneficial effect on skills learning as pretraining VAD with TE, but avoid drawbacks of TE. Methods: Three hundred twenty-two third-year medical students were randomized into 3 groups (the control [C], TE, SE). A videotaped BLS skills pretest was conducted in 3 groups. Then, group C received traditional training with concurrent feedback. Video-assisted debriefing with TE in the pretest or SE was delivered in groups TE or SE, respectively, followed by BLS training without any feedback. Basic life support skills were retested 1 week later (posttest). Students completed a survey to express their preference to TE or SE for VAD in the future. Results: Higher BLS skills scores were observed in groups TE (85.7 ± 7.0) and SE (86.8 ± 7.5) in the posttest, compared with group C (68.7 ± 13.3, P < 0.001). No skills difference was observed between group TE and SE in the posttest. More trainees (65.8%) preferred SE for VAD. Conclusions: Pretraining VAD with SE had an equivalent beneficial effect as VAD with TE on BLS skills learning in medical students. More trainees preferred SE for VAD with regard to psychological safety. Abstract : Supplemental digital content is available in the text.